A Study on Financial Derivatives (Futures & Options) and Development of Financial Derivatives Market in India: Role of retail investors in the development of financial derivatives market in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The growth of the equity derivative business has been an unprecedented one. The retail and institutional investors occupied a key role in development of derivatives trading in India. It is been known that most of the contributors in equity derivatives are Retail investors (which includes small brokers trading for themselves) have contributed 51.04 higher when comparing with institutional investment. Higher portion of funds where poured by retail investors.